Pro-Poor Tourism: A Case Study of Melaka UNESCO World Heritage City - Ab Rahman, Syakir Amir; Mohit, Mohammad Abdul; Bachok, Syahriah (2014)
The concept of Pro-Poor Tourism has been significant for over 10 years. The concept has been given a priority at every level of tourism agenda in most less developed as well as developing countries, as it is believed that involving the poor community can eradicate poverty. Malaysia’s ‘vision 2020’ aspiration to join the league of developed nation that was inspired by former Prime Minister, Mahathir two decades ago struggling herself to eradicate the poor, and becoming as a high income developed nation. The primary aim of this study addresses exploring Melaka as the best example in implementing the Pro-Poor Tourism in Malaysia. A state that has been claimed as UNESCO World Heritage City in 2008 has successfully decreased the poverty rate from 1.8% in 2007 to 0.1% in 2012. Correlation result between poverty rates and tourist arrivals before and after the UNESCO declaration shows the tourist arrival gives a significant contribution to the decrease of poor. In fact, Melaka State Government with state tourism players have proposed various strategies and programs to attract domestic as well as foreign tourists. This effort has swiftly increase poor to participate in the tourism industry.